ANALISIS KARAKTERISTIK PENYERAPAN TENAGA KERJA PADA PERHOTELAN DI KOTA BAUBAUSTUDI KASUS HOTEL BERBINTANG - Abdullah, Rudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
This study aims to determine the characteristics of labor in star hotels in Baubau City. This research uses quantitative descriptive analysis with data tabulation method to determine the characteristics of labor and the number of workers absorbed in star hotels. The results showed that: hotels that are able to absorb labor above 10 percent include the Grand Clarion Hotel which absorbs the largest workforce with a percentage of 17.08 percent followed by the Plaza Inn Hotel which absorbs labor of 12.73 percent then the Swiss Bell Hotel which absorbs labor of 11.65 percent of the total workforce in star hotels. While star hotels that absorb labor below 6 percent include Dragon Inn Hotel by 5.75 percent, Zenith Hotel by 5.43 percent, D'Blitz Hotel by 5.28 percent, Kubra Hotel by 3.57 percent, and Zenith Hotel by 2.48 percent. (a) the star hotel workforce is dominated by male workers; (b) the star hotel workforce is dominated by high school / vocational high school graduates; (c) the star hotel workforce is dominated by young age; (d) the average number of working hours of star hotel workers is above 48 hours per week; (e) the average star hotel is able to absorb 50 workers with a percentage of 7.7 percent.